Deep in the Alaskan woods - Harper, Karen (Karen S.) (Harper, Karen (Karen S.) Alaska wild novel., 2020)
"Alexandra Collister came to her estranged cousins' B and B in Falls Lake, Alaska, looking for a fresh start. The surrounding forest can be harsh and unforgiving--luckily, rugged wilderness tracker Quinn Mantell offers to be her guide. Still recovering from a toxic previous relationship, Alex is wary of getting too close, but when savagely deep claw marks appear outside her bedroom window, keeping her distance from Quinn is no longer an option. Then a body turns up exhibiting the same ruthless slash marks, and Alex knows it isn't a coincidence. Something sinister is lurking in the woods around Falls Lake, turning Alex's fresh start into a brutal game of survival. The murky veil of forest offers more threats than answers. Can Alex and Quinn find the killer before darkness falls for good?"--Provided by publisher.